Providensi Allah Bagi Umat-Nya Dalam Kitab Ester Dan Relevansinya Bagi Masa Kini - Pelealu, Nadia Blessy; Harti, Sri Dwi (Views : Jurnal Teologi dan Biblika, 2024)
The book of Esther presents a deep understanding of God's providence, even though the Lord's name is not explicitly mentioned. This raises the question of how God's hidden actions can be understood and applied to present-day situations, especially in the face of seemingly random or unexpected challenges. This article aims to explore how God's providence is revealed through events in the Book of Esther and how these principles can be applied in the context of contemporary life, providing an understanding that God always works through individuals and events to fulfill His purposes. This research utilized a qualitative method with a literature review approach. Data was collected from primary sources such as the Book of Esther and secondary references including relevant theological books, Bible commentaries, journals and online articles. Analysis was conducted using inductive reasoning to understand the events in the Book of Esther in the context of God's providence. The results show that God's providence is seen in seemingly coincidental events, such as Esther's appointment as queen, King Ahasuerus' change of heart, as well as the revelation of Haman's evil plan. The book emphasizes that God, although not directly visible, is always present to lead and care for His people. In today's context, this providence inspires courage, faith, and trust in God, especially in difficult or uncertain situations.